The role of startups and business incubators in achieving economic development: The case of Saudi Arabia - Zahia, Gharbi; Naima, Barka; Zineb, Chetiba (The International tax journal, 2025)
The study aimed to highlight the role of both business incubators and emerging institutions in achieving economic development, and to shed light on the mechanisms that business incubators follow while accompanying emerging institutions, as well as the role that emerging institutions play in advancing economic development and standing in the national economy, where light was shed on each The variables of the study, where we followed the descriptive analytical approach to familiarize ourselves with the subject, and took the Saudi experience as an example. The study concluded that emerging institutions in Saudi Arabia have a fundamental and effective role in achieving economic development.